STRENGTHENING UNDERSTANDING OF NATIONAL ASSESSMENT QUESTION MATERIAL THROUGH REVIEW OF QUESTION MATERIAL AND INTRODUCTION TO COMPUTER DEVICES IN CLASS V STUDENTS OF KANDANGAN STATE PRIMARY SCHOOL - Muhammad Dimas Rahmadani; Mahardika Darmawan K.W (P3I UMSurabaya, 2024)
The researcher's aim in studying this phenomenon is based on the National Assessment replacing the PBB which is designed as an evaluation carried out by the government to assess the quality of educational services in educational units with the aim of improving and increasing the quality of student learning on an ongoing basis. This requires careful preparation from both educators and students. ANBK questions consist of reasoning questions which make students feel confused when working on them. Therefore, a strategy is needed by teachers to provide additional study hours for students to review and discuss the questions that will be tested during ANBK implementation. Apart from that, students are also trained to know and operate computers, which is the most important part of preparing students for ANBK.